The Cross-Channel Diffusion of the French May - Claire Mansour (Revue Française de Civilisation Britannique)
The well-known events of May 1968 in France struck a chord with British radical left activists. This paper examines the impact of the French May on British protest thanks to the analysis of diffusion processes between France and the United Kingdom. Because they perceived similarities between the two contexts, British protesters could identify with their French counterparts, thus providing the necessary condition for diffusion processes to occur. Information was then transferred through the mass media and the alternative press, as well as through personal contacts between both groups. British activists adopted the collective action frames and some of the tactics of the French May. Frustrated by their lack of participation in the running of their universities and workplaces, British students and workers chose to occupy their institutions, to create alternative organisational structures where they would be involved in the decision-making process. Finally, in spite of its particular historical context, Northern Ireland was also influenced by the French May, eclipsing for a brief moment, the local revolutionary Republican tradition.